2020
DOI: 10.1021/acsnano.0c00381
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Actuator Fabricated by Dynamic Asymmetric Femtosecond Bessel Beam for In Situ Particle and Cell Manipulation

Abstract: Microscale intelligent actuators capable of sensitive and accurate manipulation under external stimuli hold great promise in various fields including precision sensors and biomedical devices. Current microactuators, however, are often limited to a multiple-step fabrication process and multimaterials. Here, a pH-triggered soft microactuator (<100 μm) with simple structure, one-step fabrication process, and single material is proposed, which is composed of deformable hydrogel microstructures fabricated by an asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…Since the swelling factors of the hydrogels are closely related to the exposure dose, programming such a dose spatially on the Bessel ring leads to facile fabrication of anisotropic structures. Li generated a heterogeneous light field during the fabrication process, resulting in microtubes with asymmetric swelling/shrinking properties that exhibited reversible bending and reverting to an upright conformation within 1 s when the solution pH value changed (Figure 4b) [86]. He also demonstrated the application of this type of effective microgripper for trapping and releasing PS particles and neural stem cells.…”
Section: Phmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the swelling factors of the hydrogels are closely related to the exposure dose, programming such a dose spatially on the Bessel ring leads to facile fabrication of anisotropic structures. Li generated a heterogeneous light field during the fabrication process, resulting in microtubes with asymmetric swelling/shrinking properties that exhibited reversible bending and reverting to an upright conformation within 1 s when the solution pH value changed (Figure 4b) [86]. He also demonstrated the application of this type of effective microgripper for trapping and releasing PS particles and neural stem cells.…”
Section: Phmentioning
confidence: 97%
“…As shown in Figure 4a, the distance between two adjacent rings can be varied from 11.4 μm to 7.2 μm such that objects with specific sizes can pass through or be intercepted selectively. [86], Copyright © 2020, American Chemical Society. (c) Complex 3D micro-umbrella, which can be constructed to achieve rapid, precise, and reversible articulated-lever folding by varied pH value.…”
Section: Phmentioning
confidence: 99%
“…The swarming behavior of the m‐bots not only broadens the scope of understanding related to self‐assembly behavior in natural living systems as introduced in Section 4.7, but also brings out the potential for applications such as the multiple cargo manipulation, [ 273,396,397 ] antidiffusion by the swarming m‐bots, [ 287 ] enhanced delivery capability ( Figure a), [ 398 ] reconfigurable adjustment of the energy delivery dose for enhanced magnetic hyperthermia (Figure 21b), [ 399,400 ] and cell alignment (Figure 21c) and manipulation of intracellular organelles. [ 401 ] The in vivo swarming behavior of biological and artificial m‐bots have been investigated and explored, and it has been verified that the collective motion behavior of micro‐/nanoagents can commonly realize the enhanced delivery of drugs and energy.…”
Section: Biomedical Applications Of M‐botsmentioning
confidence: 99%
“…The use of stimulus-responsive photoresists for TPP has facilitated development of different micro/nano-actuators. Recently, Li et al [139] reported a pH-triggered soft microgripper (<100 μm) with four fingers using a poly (acrylic acid)-based hydrogel for capturing microparticles and cells. As discussed above, carboxyl (-COOH) in the side chain played an important role in the deformation triggered by a pH value change.…”
Section: Tpp For Medical Applications 41 Cell Engineeringmentioning
confidence: 99%